2021
DOI: 10.3390/ani11113029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inositol Supplementation in Sperm Extender on the Quality of Cryopreserved Mesopotamian Catfish (Silurus triostegus, H. 1843) Sperm

Abstract: This study was based on the determination of post-thaw semen quality, oxidant–antioxidant status and DNA-damage status of frozen Mesopotamian catfish semen. To this end, the sperm was frozen in diluent containing different inositol concentrations (5, 10, 20 and 40 mg). Increasing levels of inositol linearly increased the spermatozoa motility rate and duration significantly (p < 0.05). High doses of inositol increased antioxidants and decreased oxidants. In addition, lower intracellular DNA damage and percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
(108 reference statements)
1
2
0
Order By: Relevance
“…In contrast, SMCP was significantly increased in the myo-inositol group compared to the control group. This result is consistent with previous studies in human and animal sperm, showing that myo-inositol treatment in cryopreserved semen decreased oxidative stress and apoptosis, increased the cryosurvival rate, and improved gene expression [ 24 , 26 , 54 , 65 , 67 , 68 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, SMCP was significantly increased in the myo-inositol group compared to the control group. This result is consistent with previous studies in human and animal sperm, showing that myo-inositol treatment in cryopreserved semen decreased oxidative stress and apoptosis, increased the cryosurvival rate, and improved gene expression [ 24 , 26 , 54 , 65 , 67 , 68 ].…”
Section: Discussionsupporting
confidence: 93%
“…The freeze–thaw process is stressful to sperm, and during this process, sperm confront prolonged stress and increase ROS production, which leads to DNA fragmentation, changes in membranes, and cell apoptosis. Multiple studies report strong beneficial effects of myo-inositol on protecting sperm DNA and reducing ROS and apoptosis during cryopreservation [ 25 , 65 , 66 ]. Our study investigated the effect of different myo-inositol concentrations on boar sperm and evaluated oxidative stress and apoptosis parameters, including caspase activity, apoptosis index, ROS levels, and related genes, as shown in Figure 2 C, Figure 3 , and Figure 5 B.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Condorelli et al reported that MYO enhanced the motility of sperm retrieved following the swim-up procedure in both fertile and infertile individuals [129]. Furthermore, an MYO-supplemented freezing extender showed reduced OS and improved freeze-thaw sperm quality in different species including dogs [130], fish [131], bucks [132], and humans [133]. Similar results were observed when MYO supplementation was used during thawing procedures [134].…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 78%